1985
DOI: 10.1007/bf01906739
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the thyroid state on myocardial myosin in the adult pig heart

Abstract: The influence of hyper- and hypothyroidism on atrial and ventricular myosin structure and Ca2+-activated ATPase activity has been analyzed in adult mini-pigs. Whereas no difference could be demonstrated between hypo- and euthyroid ventricular myocardium, Ca2+-activated ATPase activity was significantly higher in the hyperthyroid than in the hypo- or euthyroid state. Using pyrophosphate electrophoresis and isoelectric focusing of subfragment 1 this could be ascribed to an additional ventricular myosin in the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1986
1986
1996
1996

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…It has also been reported that excessive thyroid hormone may induce tissue injury. Thyrotoxic myopathy (8) and myocardial insufficiency (9) are well known examples of tissue damage due to the direct action of thyroid hormone on target tissues. The pathophysiological basis of these abnormalities is not clear.…”
mentioning
confidence: 99%
“…It has also been reported that excessive thyroid hormone may induce tissue injury. Thyrotoxic myopathy (8) and myocardial insufficiency (9) are well known examples of tissue damage due to the direct action of thyroid hormone on target tissues. The pathophysiological basis of these abnormalities is not clear.…”
mentioning
confidence: 99%